Sovereign Credit Rating Announcements and Liquidity Shocks in the Lebanese Daily Foreign Exchange Market - Azar, Samih Antoine (International Journal of Accounting & Finance Review, 2020)
Sovereign credit rating announcements are usually unexpected events that can affect local financial markets either favorably or detrimentally. In Lebanon, the credit outlook witnessed a deteriorating trend since the mid of the year 2016. The major hypothesis of this paper is that the reaction to the bad credit rating announcements is statistically significant, although ephemeral, delimited to just a few days. It is through the liquidity channel that these announcements create uncertainty and affect the economy. There are two related hypotheses: (1) illiquidity shocks impact undesirably the financial markets, and (2) credit rating announcements are accompanied by a surge in illiquidity. Since the impact of these announcements is ephemeral it should be assessed by high-frequency data, or at most by daily financial data. The domestic foreign exchange market is an ideal place to study this impact. Fortunately, the central bank of Lebanon has lately made available daily foreign exchange rates for six major currencies beginning in 2010. This defines six multiple regressions that are constructed to differentiate between the short-run and the long-run responses to illiquidity. The empirical results show that the above two hypotheses are strongly supported. Moreover, it matters little whether the event window is 3, 4 or 5 days. JEL Classification: G14, F31, C58, C38.